Isolating the role of time in bed restriction in the treatment of insomnia: a randomized, controlled, dismantling trial comparing sleep restriction therapy with time in bed regularization. Issue 11 (18th May 2020) - Maurer, Leonie Franziska; Espie, Colin Alexander; Omlin, Ximena; Reid, Matthew James; Sharman, Rachel; Gavriloff, Dimitri; Emsley, Richard; Kyle, Simon David
Abstract: Study Objectives: Sleep restriction therapy (SRT) is one of the most effective treatments for insomnia. Restriction of time in bed (TIB) is assumed to be the central mechanism through which SRT improves sleep consolidation and reduces insomnia symptoms. This hypothesis has never been directly tested. We designed a randomized, controlled, dismantling trial in order to isolate the role of TIB restriction in driving both clinical and polysomnographic sleep outcomes. Methods: Participants aged 25–55 who met diagnostic criteria for insomnia disorder were block-randomized (1:1) to 4 weeks of SRT or time in bed regularization (TBR), a treatment that involves the prescription of a regular but not reduced TIB. The primary outcome was assessed with the insomnia severity index (ISI) at baseline, 4-, and 12-weeks post-randomization. Secondary outcomes included sleep continuity (assessed via polysomnography, actigraphy, and diary) and quality of life. We performed intention-to-treat analyses using linear mixed models. Results: Fifty-six participants (39 females, mean age = 40.78 ± 9.08) were assigned to SRT ( n = 27) or TBR ( n = 29). Daily monitoring of sleep via diaries and actigraphy confirmed large group differences in TIB ( d range = 1.63–1.98). At 4-weeks post-randomization, the adjusted mean difference for the ISI was −4.49 ( d = −1.40) and −4.35 at 12 weeks ( d = −1.36), indicating that the SRT group reported reduced insomnia severity relative to TBR. Robust treatment effects in favor of SRT were also found for objective and self-reported sleep continuity variables ( d range = 0.40–0.92) and sleep-related quality of life ( d = 1.29). Conclusions: For the first time, we demonstrate that TIB restriction is superior to the regularization of TIB on its own. Our results underscore the centrality of the restriction component in reducing insomnia symptoms and consolidating sleep.